Pengembangan Komoditas Unggulan Tanaman Pangan Propinsi Sumatera Barat - Elara Resigia; Syahrial Syahrial (TATALOKA, 2020)
The development of food crops commodities is one of the priorities of the National Medium-Term Development Plan (RPJMN) 2015-2019 of the Ministry of Agriculture of Indonesia in terms of guarantee of food availability. West Sumatra Province is one of the central areas of production of food crops commodities in Indonesia. The objectives of this research are 1) to analyze food crops of West Sumatera Province; 2) to analyze the availability and completeness of facilities for the development of superior commodities of food crops; and 3) to formulate the strategy of developing the superior commodities of food crops. The data used in this research covers the area of harvest, the number of production, and the number of facilities area by time series (2011-2015). Data analysis used in this research include LQ, scalogram and SWOT analysis. The results showed rice commodity as a pre-eminent commodity in West Sumatera Province. There are six areas of development of commodities seeded rice that is in the hierarchy I. SWOT matrix analysis results obtained some superior commodity development strategies include; SO strategy 1) Establish and enhance the role of partnership with all stakeholders (government, farmers, traders, and cooperatives); 2) the use of agricultural cropping technology; WO strategy; 1) Development of agricultural development infrastructure (irrigation channel, village axis road) and application of agricultural technology (cultivation); 2) Institutional strengthening of farming capital; strategy ST: 1) Leading commodity marketing policy / regulation by West Sumatera Provincial Government, 2) Gapoktan and Farmers Household (RTP) Empowerment 1); WT strategy: 1) Development and training of management and marketing of agricultural products by government 2) Optimalization of institutional function and capital of farming to support improvement of marketing quality of agricultural products